Multicycle investigation of a sol‐gel‐derived Fe2O3/ATP oxygen carrier for coal chemical looping combustion. Issue 4 (19th November 2015) - Guo, Qingjie; Yang, Mingming; Liu, Yongzhuo; Yang, Qinqin; Zhang, Yunpeng
Abstract : Fe‐based oxygen‐carrier particles with attapulgite (ATP) as a support material for coal chemical looping combustion (CLC) have been prepared using a sol‐gel approach. The multiredox characteristics of the prepared Fe4ATP6 (Fe2 O3 to ATP mass ratio of 40:60) were experimentally examined in a batch fluidized bed reactor at 900°C. The experimental results indicated that the synergistic reactions between ATP and Fe2 O3 increased the coal conversion. Fe4ATP6 exhibited high reactivity, particularly for low‐rank coals, in the CLC process. The improved pore structure and surface area were responsible for the high reactivity of Fe4ATP6. In 60 redox cycles, H2 was mainly generated in the outlet gas as the carbon conversion efficiency had reached 95%, and both the coal combustion efficiency and CO2 capture efficiency were greater than 95%. © 2015 American Institute of Chemical Engineers AIChE J, 62: 996–1006, 2016